2015
DOI: 10.1021/acs.bioconjchem.5b00290
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer-Linked Antifreeze Proteins Have Superior Activity and Thermal Recovery

Abstract: By binding to ice, antifreeze proteins (AFPs) depress the freezing point of a solution and inhibit ice recrystallization if freezing does occur. Previous work showed that the activity of an AFP was incrementally increased by fusing it to another protein. Even larger increases in activity were achieved by doubling the number of ice-binding sites by dimerization. Here, we have combined the two strategies by linking multiple outward-facing AFPs to a dendrimer to significantly increase both the size of the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…Studies from the laboratories of Tsuda, Davies, and Holland have demonstrated that the multimerization of native type III AFP can increase TH activity [210,211,212]. Recently, Steven et al claimed the dendrimer-like AFPs showed higher TH values [213], and Phippen et al demonstrated 12 AFP-fused protein cage nanoparticles that increased the TH value to more than 50-fold that of monomeric AFP [214]. A few groups have attempted to synthesize AFP or AFGP derivatives to elucidate the underlying mechanism of action and to develop practical applications [215,216,217,218,219,220,221].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Studies from the laboratories of Tsuda, Davies, and Holland have demonstrated that the multimerization of native type III AFP can increase TH activity [210,211,212]. Recently, Steven et al claimed the dendrimer-like AFPs showed higher TH values [213], and Phippen et al demonstrated 12 AFP-fused protein cage nanoparticles that increased the TH value to more than 50-fold that of monomeric AFP [214]. A few groups have attempted to synthesize AFP or AFGP derivatives to elucidate the underlying mechanism of action and to develop practical applications [215,216,217,218,219,220,221].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“… 24 To address this, we have investigated (supramolecular) branched PVAs and found that addition of a third arm to a PVA has no effect on IRI activity, 25 as has been seen for branched AFPs. 26 This is significant, as although the molecular weight was increased, there was no enhancement compared to increasing the molecular weight of a linear polymer. Brush-like PVA also shows identical activity to linear equivalents 12 despite having far higher molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is similar to AFPs that do not bind to the basal {0001} planes. 9 As illustrated in Figure 3A, the TH activity for S + Cl -(0.31 kDa) is less than that reported for TmAFP (9 kDa; 9,10 ) and AFPIII (7 kDa; 10,33 ), but similar to the glycoprotein AFGP8 (2.6 kDa). 34 The growth velocity along the a-axis was negligible until the sudden burst of growth as the temperature was lowered, precluding measurement of growth velocity along this direction.…”
Section: Resultsmentioning
confidence: 66%